THE INFLUENCE OF VISUAL MERCHANDISING ELEMENTS ON SHOPPER’S IMPULSE BUYING MOTIVES - Aniza Suriati binti Abdul Shukor; GOVINDARAJOO, PHAVIITHTIRRAH; Fazlina binti Abd Rahiman (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
THE INFLUENCE OF VISUAL MERCHANDISING ELEMENTS ON SHOPPER’S IMPULSE BUYING MOTIVES Phaviithtirrah A/P Govindarajoo 1, Aniza Suriati binti Abdul Shukor2 Fazlina binti Abd Rahiman3 Politeknik Sultan Azlan Shah¹, Politeknik Sultan Azlan Shah², Politeknik Sultan Azlan Shah, Behrang, Perak³ Politeknik Sultan Azlan Shah Behrang 35950 Perak Malaysia phaviithtirrah@psas.edu.my ABSTRACT: Visual Merchandising is showing merchandise and concepts at the retailer’s very best with the end purpose of making sales. The primary purpose of this study was to examine what visual merchandising elements are the most influential on shoppers in the Sports Direct Sunway Pyramid when shopping in sports, fitness, fashion and lifestyle fascia’s & brands. A total of 100 respondents participated in the survey. The study used a non-probability sampling technique which is convenience sampling. The respondents were customers of a Sports Direct Sunway Pyramid. The data were processed using the Statistical Packages for Social Sciences (SPSS) version 23. The researchers have identified three main elements of visual merchandising: window display, mannequin display and floor merchandising. The value of the correlation coefficient is 0.695. The outcomes showed that shopper's impulse buying is significantly influenced by window displays, mannequin displays and floor merchandising. The study also concludes that the Mannequin display had the highest positive influence on shoppers' impulse buying and floor merchandising has the least significant effect on shoppers' impulse buying motives in the Sports Direct Sunway Pyramid. To entice customers into their store, the merchant must thus comprehend the demands and wishes of the shoppers and produce the ideal exhibition of the shoppers' expectations. Keywords: Visual Merchandising, Window Display, Mannequin Display, Floor Merchandising, And Impulse Buying Motives